Supervision as an educational activity in clinical psychology training programs: conceptions on its core characteristics and implementation (2014)
During the first stage of an educational evaluation study, a qualitative exploration has been conducted on conceptions that clinical supervisors hold in regard to the characteristics of supervision as an educational activity in higher education programs. Hence, 10 clinical supervisors affiliated with a bachelor’s program in psychology and a master’s program in clinical psychology –both offered by a private university at Bogotá, Colombia- were enrolled as voluntary participants. Data were collected by means of a semi-structured interview and responses were analyzed using the NCT method (Friese, 2012). Software for qualitative analysis was also used in this study. Results include descriptors of supervision’s basic characteristics, participants’ roles and ideal scenarios of implementation. Additionally, this study reveals some critical issues related to: 1) the nature of supervision in the bachelor’s program and its similarities and differences when compared to a mentoring process (Milne, 2009); and 2) the perceived emphases of supervision in skills training versus development of competencies. Conducting further research aimed to a contextualized and deep understanding of the pedagogical functioning of these educational programs is needed in order to methodologically triangulate and enrich the validity of the abovementioned findings.